(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Collective efforts are needed on the part of society and the government to put an end to the practice of child labor. In fact, every citizen should take a pledge to never employ child laborer, rather discourage others too from doing so. We should create awareness amongst people employing child laborers and the parents sending their children to work. We need to provide our children a happy childhood where they are able to enjoy the best period of their lives with a merry and carefree attitude. The government should make efforts to increase the incomes of parents by launching various development schemes. Efforts should be made towards poverty eradication combined with educational reforms to provide free or affordable access to quality education. Only by taking comprehensive steps, the Government can hope to eliminate all forms of child labor by 2020.